Materiality, Reinvention and History Leopardo al sol by Laura Restrepo and Santa Suerte by Jorge Franco (2023)
The following article establishes a dialogue on narrative fiction and its relevance within the contemporary Colombian historical account, taking into consideration scenarios of constant intersection. More than a decade after the Agreement for Historical Truth and Reparation and the consolidation of the work carried out by Centro Nacional de Memoria Histórica, which began almost ten years ago with its first report, it is worth revisiting some ideas related to how history is narrated in Colombia. Indeed, the historical value of fiction will be argued, along with the vitality of its diverse social and cultural actors, giving rise to invaluable intersectionality in the collective memory, in its materiality, and in its historical reinvention. Fictional texts, therefore, offer paths for reinventing historical narratives that do not replace them, but rather empower their participants/speakers, their readers/receivers, and their versions/accounts within the processes of national and human memories in present Colombia. The significance of this proposal will come from the inclusiveness and pluralism of these narratives and not from the moral judgment imposed by an authoritative and singular narrative voice.